MAPPING MEANING: A DISCOURSE-PRAGMATIC LENS ON DEIXIS IN ACADEMIC WRITING - Hartati, Yulia Sri; Bahardur, Iswadi; Silvia, Annisa (ppjbsip, 2025)
Deixis, as a key pragmatic feature, plays an important role in structuring meaning, positioning the writer, and guiding the reader through academic texts. This study investigates the use and function of different deixis categories in research proposals written by students, intending to reveal their role in academic positioning and reader engagement. Adopting a pragmatic approach, five research proposals from scientific writing were purposively selected. The analysis identified five primary types of deixis—person, time, place, discourse, and social—each serving distinct rhetorical purposes. Person deixis was found to be crucial in negotiating writer–reader relationships, while time deixis organized the research narrative chronologically and signaled methodological procedures. Place deixis localized the research context, discourse deixis ensured textual cohesion, and social deixis indexed academic politeness and formality. The findings reveal that while students demonstrate basic control over deictic expressions, there is limited strategic use of deixis for building stance, engagement, and argumentation strength. This suggests a pragmatic competence gap affecting the persuasive and coherent delivery of research proposals. The study highlights the pedagogical implications of integrating pragmatics into academic writing instruction, enabling novice writers to position themselves within the academic community effectively. This research contributes to the growing body of pragmatic studies by focusing on an underexplored genre, research proposals within scientific writing. Future research is recommended to expand the dataset, include cross-linguistic comparisons, and explore multimodal deixis in digital academic submissions. This study provides valuable insights for improving research writing pedagogy and fostering advanced academic literacy skills by deepening the understanding of how deixis shapes academic discourse.